Innovative macroporous granules of nanostructured-hydroxyapatite agglomerates: Bioactivity and osteoblast-like cell behaviour - M. S. Laranjeira (2010)
To modulate the biological response of implantable granules, two types of bioactive porous granules composed of nanostructured-hydroxyapatite (HA) agglomerates and microstructured-HA, respectively, were prepared using a polyurethane sponge impregnation and burnout method. The resulting granules presented a highly porous structure with interconnected porosity. Both types of granules were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEMI, and mercury intrusion porosimetry. Results showed that nanostructed-HA granules presented higher surface area and porosity than microstructured-HA granules. In vitro testing using MG63 human osteoblast-like cells showed that on both types of surfaces cells were able to adhere, proliferate, and migrate through the macropores, and a higher growth rate was achieved on nanostructured-HA granules than on microstructured-HA granules (76 and 40%, respectively). In addition, these cells maintained similar expression levels of osteoblastic-associated markers namely collagen type I, alkaline phosphatase, bone morphogenetic protein-2, macrophage colony-stimulating factor, and osteoprotegerin. These innovative nanostructured-HA granules may be considered as promising bioceramic alternative matrixes for bone regeneration and drug release application. (C) 2010 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 95A: 891-900,2010.